Dignity of Gainful Employment. The Perspective of An Academic Teacher - Hanna MACKIEWICZ (Communications of International Proceedings, 2021)
Dignity is a mysterious concept, difficult to grasp. The term ‘dignity’ related to a specific person, on the one hand, involves a sense of value that makes an individual act according to certain rules, and on the other hand, the respect he earns from others. In gainful employment, an employee may shape his dignity by perfecting his job and in cooperation with others. When a person’s actions in his work are appreciated by others, he is almost sure that he is working in the right place, working like for himself, independently. The article presents the results of a qualitative study on the importance of dignity of gainful employment from the perspective of an academic teacher, including remote work during a pandemic. On the one hand, respondents indicate the importance of dignity at work, and on the other, they point to many areas of disrespect for the dignity of their work.
Keywords: Dignity of Gainful Employment; Academic Teacher’s Work; Conditions of Gainful Employment